PENGARUH KOMPOSISI DAN WAKTU FERMENTASI CAMPURAN LIMBAH INDUSTRI TAHU DAN KOTORAN SAPI TERHADAP KANDUNGAN GAS METHANE PADA PEMBANGKIT BIOGAS - Mohammad Nurhilal; Purwiyanto Purwiyanto; Galih Mustiko Aji (P3M Politeknik Negeri Indramayu, 2020)
Biogas is alternative energy produced from the anaerobic activity process of methane bacteria obtained by fermentation. Anaerobic activation is a sequence of microorganism processes breaking down biodegradable materials without oxygen. Biogas is mostly produced from cow dung and tofu industry waste that has the potential to contain methane (CH4), carbon dioxide (CO2) and hydrogen sulfide (H2S). To reduce the content of (CO2) and (H2S) and to increase the element of methane gas, the purification process is needed to do. Purification can be carried out by absorption techniques using water, NaOH solution, and zeolite/silica gel. The purpose of this study is to examine the methane gas content of variations in the composition of cow dung and tofu liquid waste and the fermentation time. The method used was an experiment by varying the composition of cow dung and tofu liquid waste by 40%: 60%; 50%: 50%; and 60%: 40%, as well as variations in the fermentation time of120, 168 and 216 hours of fermentation. The results showed that the highest methane gas content in the composition of a mixture of cow dung and tofu liquid waste was 50:50 in 168 hours of fermentation which was equal to 2.806%. The content of methane gas was influenced by the fermentation time, the pH conditions in the digester, and the intensity of stirring the biogas material in the digester.